2010
DOI: 10.1007/s10764-010-9445-z
|View full text |Cite
|
Sign up to set email alerts
|

Focusing Conservation Efforts for the Critically Endangered Brown-headed Spider Monkey (Ateles fusciceps) Using Remote Sensing, Modeling, and Playback Survey Methods

Abstract: Brown-headed spider monkeys (Ateles fusciceps), endemic to the ChocoDarien forests and lower Andean forests of NW Ecuador, are considered critically endangered. Unfortunately, scientific data regarding the actual status of populations is lacking. We combined satellite image analysis, species-specific habitat assessment, and a field survey technique using playback to focus conservation efforts for this species. First, we identified remaining forest via a LANDSAT mosaic and then applied species-specific criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(46 citation statements)
references
References 19 publications
0
35
0
2
Order By: Relevance
“…A distribution model developed by Peck et al (2011) identified potential spider monkey habitat in Northwestern Ecuador that included both of our study sites. Our physical comparison of the two forests showed no obvious structural reason for the observed differences in primate abundances at the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…A distribution model developed by Peck et al (2011) identified potential spider monkey habitat in Northwestern Ecuador that included both of our study sites. Our physical comparison of the two forests showed no obvious structural reason for the observed differences in primate abundances at the two sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cette augmentation est prédite à 141,35% pour RCP 2.6 et 216,72% pour le scénario 8.5. (Peck et al, 2010). Il peut donc se passer de données d'absence pour fonctionner.…”
Section: Discussionunclassified
“…Entre las especies de fauna están Ateles fusciceps fusciceps Mono Araña, Cephalopterus penduliger Pá-jaro Paraguas y Ara ambiguus Guacamayo de la Costa; y entre los árboles, la última población importante de Lecythis ampla Miers, Salero, un árbol que produce enormes frutos, cuyas semillas son alimento para el Guacamayo de Costa [W.A. Palacios, datos sin publicar; 29,30,31]. Asimismo, se han visto especies de Aspidosperma, Myrcianthes, Otoba, todas especies de árboles no registradas para la flora de Ecuador (y posiblemente nuevas para la ciencia) (W.A.Palacios, datos sin publicar).…”
Section: Otoba Gordoniifolia Antioquia a Costa De Ecuadorunclassified